Fast functional modelling of diode-bridge rectifier using dynamic phasors - Yang, Tao; Bozhko, Serhiy; Asher, Greg (IET, 2015)
In this paper, a functional model for diode-bridge rectifiers is developed based on the dynamic phasor concept. The developed model is suitable for accelerated simulation studies of the electric power systems under normal, unbalanced and line faulty conditions. The high accuracy and efficiency of the developed model have been demonstrated by comparison against three-phase time-domain model and against the model employing synchronous space-vector representations. The experimental verification of the developed model is also reported. In addition, an error analysis shows that the error of the developed model is less than 10% at the most severe unbalanced conditions. The prime purpose of the model is for the simulation studies of more-electric aircraft power architectures at a system level; however it can be directly applied for simulation study of any other electrical power system interfacing with uncontrolled diode bridge rectifiers.